2021
DOI: 10.2478/scjme-2021-0009
|View full text |Cite
|
Sign up to set email alerts
|

Energy Analysis of HFC-152a, HFO-1234yf and HFC/HFO Mixtures as a Direct Substitute to HFC-134a in a Domestic Refrigerator

Abstract: The Kyoto protocol emphasized the need of replacement of HFC refrigerant due to their high GWP values that causes pollution in the environment. So in this paper the refrigerants R1234yf, R152a and HFOs/HFCs mixtures of R134a/R152a/R1234yf such as ARM42 (in the ratio of 8.5/14 /77.5 by mass), ARM42a (in the ratio of 7/11/82 by mass) with a view of replacement of the refrigerant HFC-134a in a domestic refrigerator were analyzed theoretically. Volumetric cooling capacity, compressor discharge temperature, coeffic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 8 publications
0
1
0
Order By: Relevance
“…The study by Yang et al [13] found that energy consumed was reduced by 3.5 percent and the refrigeration capacity was increased, while the excellent mass of charge, which was 80 grams, decreased to 5.9%. Hasheer et al [14] performed energy analyses of R-152a, R-1234yf, and HFC/HFO blends as a direct alternative to R-134a in a domestic refrigerator. They used blends of R134a/R152a/R1234yf like ARM42 (in the ratio of 8.5/14 /77.5 by mass) and ARM42a (in the ratio of 7/11/82 by mass) as alternatives to R134a and theoretically analysed them.…”
Section: Introductionmentioning
confidence: 99%
“…The study by Yang et al [13] found that energy consumed was reduced by 3.5 percent and the refrigeration capacity was increased, while the excellent mass of charge, which was 80 grams, decreased to 5.9%. Hasheer et al [14] performed energy analyses of R-152a, R-1234yf, and HFC/HFO blends as a direct alternative to R-134a in a domestic refrigerator. They used blends of R134a/R152a/R1234yf like ARM42 (in the ratio of 8.5/14 /77.5 by mass) and ARM42a (in the ratio of 7/11/82 by mass) as alternatives to R134a and theoretically analysed them.…”
Section: Introductionmentioning
confidence: 99%
“…R161 will need to be redesigned completely before it can be used as a replacement, according to the authors. Many researchers conducted various experimental works in the domestic refrigerator to enhance the performance of the system with low GWP refrigerants and blend with R134a as a forthcoming alternative replacement in the refrigeration system 12 – 23 . Baskaran et al 24 – 35 examined the performance of several eco-friendly refrigerants and combinations with R134a as a prospective alternative replacement in various tests on a vapour compression refrigeration system.…”
Section: Introductionmentioning
confidence: 99%